2018
DOI: 10.3390/w10040358
|View full text |Cite
|
Sign up to set email alerts
|

Flow Velocity Effects on Fe(III) Clogging during Managed Aquifer Recharge Using Urban Storm Water

Abstract: Storm water harvesting and storage has been employed for nearly a hundred years, and using storm water to recharge aquifers is one of the most important ways to relieve water scarcity in arid and semi-arid regions. However, it cannot be widely adopted because of clogging problems. The risk of chemical clogging is mostly associated with iron oxyhydroxide precipitation; anhydrous ferric oxide (HFO) clogging remains a problem in many wellfields. This paper investigates Fe(III) clogging levels at three flow veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…higher than the final one. Similar results were reported by (Du et al, 2018;Vanderzalm et al, 2020), when they permeated the sample with a solution containing Fe (III) or water with suspended solids.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…higher than the final one. Similar results were reported by (Du et al, 2018;Vanderzalm et al, 2020), when they permeated the sample with a solution containing Fe (III) or water with suspended solids.…”
Section: Discussionsupporting
confidence: 85%
“…For example, there has been extensive research on the variation of hydraulic conductivity in groundwater artificial recharge (Konikow et al, 2001;Mays & Hunt, 2005;Siriwardene et al, 2007;Song et al, 2020;Ye et al, 2019). Vanderzalm et al (2020) and Du et al (2018) subjected sandy samples to water permeation containing suspended solids and Fe (III) ions, respectively, for an extended period (40 days in the former case and seven days in the latter study), leading to observed fluctuations in Ks that demonstrate a prevalent declining pattern over time. These studies identified physical and biological clogging mechanisms as dominant factors for Ks variation.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the mass of clogging material that was retained in the sand column, the infiltration medium was excavated at 1 cm intervals at the end of the experiments. The sand samples were immersed in hydrochloric acid and shaken vigorously to dissolve the Fe (III) clogging material [23]. The mass retained in the column, referred to as M(t), was estimated from the difference between the inlet and outlet Fe (III) concentrations:…”
Section: Experimental Methods and Procedures 221 Recharge Experimentsmentioning
confidence: 99%
“…Concerning the advisory section of the Guidelines that addresses clogging in MAR, there have been many papers since 2009 that have better-defined clogging processes (e.g., [50][51][52][53]) that would enable refinements to the current general guidance. Such refinements could include approaches to mitigate and remediate clogging, such as where statutory approvals may be required.…”
mentioning
confidence: 99%